After Interventionism: A Typology of United States Strategies. Issue 3 (3rd July 2019) - MacMillan, John
ABSTRACT: What strategies does the United States pursue when it no longer perceives overt military intervention as politically viable or desirable but the problems or issues for which it was formerly undertaken remain? This analysis identifies three such periods in American foreign policy since the United States became a World Power and draws from the work of Peter Hall to develop a typology of strategies according to the magnitude of policy change. These range from adjustment in the settings of interventionism – persistence; the substitution of alternative instruments of foreign policy – ameliorism; and the principled rejection of interventionism in conjunction with a more systematic critique of prevailing foreign policy assumptions – transformationalism. Yet each approach is beset by certain structural limits and contradictions arising from the domestic politics and constitutional-institutional system of the United States that are important in understandiing and appreciating more fully the challenges – and opportunities – of the period 'after interventionism'.